Analysis of Class VII Students' Mathematical Communication Ability in Algebra Calculating Operations - Virginia Paulina Engelina; Dadang Rahman Munandar (Equivalent: Jurnal Ilmiah Sosial Teknik, 2023)
The problem is that teachers dominate class communication by explaining concepts, showing examples, and directing questions and answers. This study aims to analyze the communication skills of junior high school students in solving algebraic arithmetic operations. The research was conducted on class VIII students of SMP Negeri 1 Rawamerta for the 2022/2023 academic year. The method used in this research is qualitative, with a descriptive approach. Data collection in this study was carried out by providing mathematical communication ability test instruments used by previous researchers. Based on the data analysis that has been done, the percentage of students communicative abilities in the average score for solving algebraic arithmetic problems is 14.58%. Understanding communication in completing algebraic arithmetic operations for class VIII students of SMP Negeri 1 Rawamerta needs to be more profound.